Distinct Roles of Outer Membrane Porins in Antibiotic Resistance and Membrane Integrity in Escherichia coli - Choi, Umji; Lee, Chang-Ro (Frontiers in Microbiology, 2019)
A defining characteristic of Gram-negative bacteria is the presence of an outer membrane, which functions as an additional barrier inhibiting the penetration of toxic chemicals, such as antibiotics. Porins are outer membrane proteins associated with the modulation of cellular permeability and antibiotic resistance. Although there are numerous studies regarding porins, a systematic approach about the roles of porins in bacterial physiology and antibiotic resistance does not exist yet. In this study, we constructed mutants of all porins in Escherichia coli and examined the effect of porins on antibiotic resistance and membrane integrity. The OmpF-defective mutant was resistant to several antibiotics including β-lactams, suggesting that OmpF functions as the main route of outer membrane penetration for many antibiotics. In contrast, OmpA was strongly associated with the maintenance of membrane integrity, which resulted in the increased susceptibility of the ompA mutant to many antibiotics. Notably, OmpC was involved in both the roles. Additionally, our systematic analyses revealed that other porins were not involved in the maintenance of membrane integrity, but several porins played a major or minor role in the outer membrane penetration for a few antibiotics. Collectively, these results show that each porin plays a distinct role in antibiotic resistance and membrane integrity, which could improve our understanding of the physiological function and clinical importance of porins.